The effects of fluorescent labels on Aβ42 aggregation detected by fluorescence correlation spectroscopy. Issue 11 (11th October 2018) - Zheng, Yanpeng; Xu, Lingwan; Yang, Jingfa; Peng, Xianglei; Wang, He; Yu, Na; Hua, Ying; Zhao, Jiang; He, Jinsheng; Hong, Tao
Abstract: Fluorescence‐based methods are promising for measuring amyloid beta (Aβ) oligomers, given their capacity to analyse a sample at the single‐molecule level. As the attachment of fluorescent labels may influence the biochemical properties of the Aβ oligomers, the effects of fluorescent labels on Aβ oligomers must be evaluated. In this paper, we compared the impacts of five different fluorescent dyes on the aggregation of Aβ42 oligomers using fluorescence correlation spectroscopy (FCS). We found that fluorescent labels of BODIPY® FL‐C5 (BP), N‐hydroxysuccinimide rhodamine B ester (RB) and rhodamine B isothiocyanate (RITC) increased the propensity of labelled Aβ42 oligomers to aggregate, whereas 6‐(fluorescein‐5‐carboxamido) hexanoic acid succinimidyl ester (5‐SFX) and fluorescein 5(6)‐isothiocyanate (5(6)‐FITC) decreased the propensity of labelled Aβ42 oligomers to aggregate. This difference originated from the different electric charges and hydrophobicity of the fluorescent dyes. These results provide valuable information for establishing different aggregation models for Aβ42 oligomers in vitro using FCS. Abstract :